JAMOLING MUSʼHAF (MUS'HAF COUNTENANCE) - Amonova, Zilola (FILOLOGIYA UFQLARI JURNALI, 2024)
Undoubtedly, Alisher Navoi is a great artist of words, who enriched the Uzbek classical literature with the world of various themes and contributed to the spiritual development of man. Themes of perfection, human divinity and dignity have a special place in the poet's work. One of them is the ghazals connected with the comparison of human beauty to mushaf (collection of books) in Navoi's lyrical heritage. It should be noted that poems on this topic are found in almost all of the works of the artist. The ghazal we are going to analyze below is given in the 232nd issue of the "Badoyi ul-bidoya" divan.